Requalifier les territoires de l’action locale - Johan Milian; Sandrine Bacconnier-Baylet (Territoire en Mouvement)
French ministry of regional planning built in 2006 a new device in order to help rural actors organize themselves for a better development; this tool was called “Pôle d’Excellence Rurale” (PER). Rural territories have used it in various ways. Some of them put a great attention on forest management and economic activity around wood energy and timber. Because of their particularities, the PER built upon such a bioresource highlight what happens in rural areas regarding social, cultural and economic changes and what can be done as collective project initiatives. They show how forest can also act as a territorial resource, how relationships between local actors are reorganized as well as the paths of development inside the rural area. The paper stresses these experimentation and dynamics around forest activity in several PER located in southern France.